Mathematical framework for multi-frequency identification of thin insulating and small conductive inhomogeneities. (2nd August 2016) - Ammari, Habib; Seo, Jin Keun; Zhang, Tingting
Abstract: We are aiming to identify the thin insulating inhomogeneities and small conductive inhomogeneities inside an electrically conducting medium by using multi-frequency electrical impedance tomography. The thin insulating inhomogeneities are considered in the form of a tubular neighborhood of a curve and small conductive inhomogeneities are regarded as circular disks. Taking advantage of the frequency dependent behavior of insulating objects, we give a rigorous derivation of the potential along thin insulating objects at various frequencies. Asymptotic formula is given to analyze relationship between inhomogeneities and boundary potential at different frequencies. In numerical simulations, spectroscopic images are provided to visualize the reconstructed admittivity at various frequencies. For the view of both kinds of inhomogeneities, an integrated reconstructed image based on principal component analysis is provided. Phantom experiments are performed by using Swisstom EIT-Pioneer Set.